2022
DOI: 10.1038/s41392-022-01042-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting signaling pathways in prostate cancer: mechanisms and clinical trials

Abstract: Prostate cancer (PCa) affects millions of men globally. Due to advances in understanding genomic landscapes and biological functions, the treatment of PCa continues to improve. Recently, various new classes of agents, which include next-generation androgen receptor (AR) signaling inhibitors (abiraterone, enzalutamide, apalutamide, and darolutamide), bone-targeting agents (radium-223 chloride, zoledronic acid), and poly(ADP-ribose) polymerase (PARP) inhibitors (olaparib, rucaparib, and talazoparib) have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 569 publications
0
33
0
11
Order By: Relevance
“…Furthermore, we found that PSMA was a specific membrane marker for tip-like ECs in non-prostate cancers. PSMA is a type II transmembrane glycoprotein with folate hydrolase and N-acetylated-α-linked-acidic dipeptidase activities [37] . PSMA has been widely used as a target for the diagnosis and treatment of prostate cancer because of its high expression in prostate cancer cells [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that PSMA was a specific membrane marker for tip-like ECs in non-prostate cancers. PSMA is a type II transmembrane glycoprotein with folate hydrolase and N-acetylated-α-linked-acidic dipeptidase activities [37] . PSMA has been widely used as a target for the diagnosis and treatment of prostate cancer because of its high expression in prostate cancer cells [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of estrogen receptors in PCa has been studied extensively, but remains a matter of debate (19,20). Considering that PCa tumor cells may use pathways other than those associated with androgen receptors as resistance mechanisms in advanced disease (21), it may be reasonable to evaluate the role of estrogen receptors in early-stage patients. A limited number of studies have investigated the role of estrogen receptors in PCa in non-metastatic castration-naive disease, and their results are conflicting (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to advances in understanding genomic landscapes and biological functions, the treatment of PCa continues to evolve. Therefore, next-generation AR signaling inhibitors, bone-targeting agents and poly(ADP-ribose) polymerase (PARP) inhibitors, agents targeting other oncogenic signaling pathways, such as cyclin-dependent kinase (CDK)4/6, AKT, wingless-type protein (WNT), and epigenetic marks, have successively entered clinical trials [ 116 ].…”
Section: Aeds and Prostate Cancermentioning
confidence: 99%